Improving the Ability to Describe Plant Characteristics Through Project-Based Learning (PjBL) Method and Electronic Media - Huda, Miftahul (Social, Humanities, and Educational Studies (SHES): Conference Series, 2022)
Education, in essence, is a conscious effort made by humans to develop their abilities and personalities. In the teaching and learning act4ities at SD Negeri 2 Bugel, it is evident that the learning outcomes of students are low, and they have not yet reached the passing grade (KKM), specifically 12 students, 7 students or 58% who have not achieved proficiency. The author str4es to address this issue through the improvement of learning by implementing the Project-Based Learning (PjBL) method as an effort to enhance the learning abilities of fourth-grade students in describing the specific characteristics of plants using electronic media at SD Negeri 2 Bugel. The research problem in this study is "Improving the Ability to Describe the Specific Characteristics of Plants Through the Implementation of the PjBL Method and the Use of Electronic Media in the subjects of Natural Sciences and Social Sciences for six-grade students at SD Negeri 2 Bugel." The aim of the research is to describe the specific characteristics of plants through the utilization of the PjBL method. The research was conducted in the fourth grade of SD Negeri 2 Bugel in September and October. The implementation of the learning improvement consisted of four stages: planning, execution, observation, and reflection. In the pre-cycle of learning improvement (Thursday, September 25, 2020), the proficiency level was 58%. In Cycle 1 (Thursday, October 2, 2020), there was an improvement with a percentage of students who passed reaching 67%, and in Cycle 2 (Thursday, October 16, 2020), the percentage of students who passed reached 100%.